Today I am going to be explaining the pythagorean theorem, which was first explained by the Greek philosopher Pythagoras. This is the way you calculate the hypotenuse of a right triangle. The equation is A squared + B squared = C squared. So, the sum of the legs of each triangle squared equals the hypotenuse. But, to get the final answer you have to find the square root of the final answer. So, for example if you had a problem that looked like this A=4, B=7, C=? then you would add the legs together. (49) + (16)=65 and then find the square root of 65, which is 8.062.